The sun doen't rises in the east (Journal of Parents and Teachers, 2014)
Astronomy is a part of the official syllabus; nevertheless this survival doesn’t correspond to an analysis of experience. What is actually what we teach and learn at school? This is what this article talks about. It also includes visits to a planetarium as a way of approaching astronomy to students and activities to do in the class or outside.
Keywords: astronomy; didactics; planetarium; solar system; observation.